Peran PCNU Mesir sebagai Aktor Multitrack Diplomacy - Makhisoh, Iis; Mujtahidah, Aida (Proceedings of Annual Conference for Muslim Scholars, 2022)
This study discusses the role of Nahdlatul Ulama Special Branch Boards (PCINU) in Egypt as an organization in multitrack diplomacy especially track 7, religion. The similarity in understanding religious moderation makes PCINU Egypt acceptable to citizens and the Egyptian government. PCINU also established cooperation with various institutions in Egypt. This research is qualitative research using a type of descriptive analysis research with a qualitative approach. Regarding data collection, the authors conducted in-depth interviews and looked for literature sources. This research concludes that PCINU Egypt has an active role in religion diplomacy efforts in Egypt. PCINU conducts religion diplomacy and promotes interrelation peace and harmony in Egypt.